Pemanfaatan Instagram Tribunnews Dalam Pembelajaran Menulis Teks Eksposisi Untuk Meningkatkan Hasil Belajar - Artawan, I Kadek Sefyan (Jurnal Penelitian Mahasiswa Indonesia, 2022)
The ever-developing technology brings many advances in life, including supporting the world of education. Even so, unfortunately there are still many teachers who have not taken advantage of technological advances. This study aims to test the learning media of the Tribunnews Instagram account in exposition text learning for class X students at Bali Mandara State High School. This research is a class action research (CAR). The results of this study indicate that exposition text learning uses news text with social media Instagram Tribunnews. The stages of this research, namely: identifying and formulating problems; analyze problems; formulate action hypotheses; make an action plan and monitor it; carry out the action and observe it; processing and interpreting data; and report. The ability to write news text in cycle 1 obtains an average value of 75 which is included in the sufficient category. After reflection and evaluation towards cycle 2, the average value rose to 85 in the very good category. Therefore, there is an increase in learning outcomes by using the Tribunnews Instagram account on the ability to write news exposition texts by class X students at Bali Mandara State High School